2022
DOI: 10.3390/ijms23073839
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral NPY Age-Related Regulation: A Comparative Analysis in Fish Translational Models

Abstract: NPY is among the most abundant neuropeptides in vertebrate brain and is primarily involved in the regulation of food intake. The NPY system is also associated with the aging process showing beneficial effects on neuronal survival via autophagy modulation. Here, we explore the age-related regulation of NPY in the brain and foregut of the shortest- and longest-lived fish species, Nothobranchius furzeri and Danio rerio, respectively. These two research models, despite some similarities, display profound biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…NPY, besides being expressed also in other tissues like spleen, kidney, and smooth muscle [66,67], interacts with a number of different appetite signals such as corticotropin-releasing factor (CRF), cortisol, CART, orexins, and galanin, suggesting that the NPY response is not exclusively dependent from the ghrelin signal [68]. In addition, NPY is involved in several other physiological functions in fish, like circadian rhythmicity, cardiovascular activity, psychomotor activity, and sexual behavior, which could have affected the present results [69][70][71].…”
Section: Discussionmentioning
confidence: 82%
“…NPY, besides being expressed also in other tissues like spleen, kidney, and smooth muscle [66,67], interacts with a number of different appetite signals such as corticotropin-releasing factor (CRF), cortisol, CART, orexins, and galanin, suggesting that the NPY response is not exclusively dependent from the ghrelin signal [68]. In addition, NPY is involved in several other physiological functions in fish, like circadian rhythmicity, cardiovascular activity, psychomotor activity, and sexual behavior, which could have affected the present results [69][70][71].…”
Section: Discussionmentioning
confidence: 82%
“…In view of the key role played by fish both in translational research [53,54] and aquaculture, our work may be of interest in different research settings. This preliminary study provides in-depth morphological data of the stomach of Nile tilapia, inspiring us to formulate a functional hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the short-lived Turquoise Killifish upregulated H3K27 methylation complexes, leading to chromatin hoarding, and downregulated H3K27 acetylation complexes in the aging process [107]. Recently, a comparative study between the short-lived Turquoise Killifish and the longer-lived zebrafish demonstrated an initial central regulation of the NPY neuropeptide in aging models, with peripheral localization being present in both ageing models, elucidating new mechanisms that warrant further study in both fish species [108].…”
Section: Complimentary With Other Animal Modelsmentioning
confidence: 99%